Associations of cholesteryl ester transfer protein (CETP) gene variants with pituitary adenoma - Sidaraite, Agne; Liutkeviciene, Rasa; Glebauskiene, Brigita; Vilkeviciute, Alvita; Kriauciuniene, Loresa (Biomedical papers, 2020)
Aim: The aim was to evaluate the association of CETP (rs5882 and rs708272) single nucleotide polymorphisms with the presence, invasiveness, hormonal activity and recurrence of pituitary adenoma (PA). Methods: The study group included 142 patients with PA and the control group, 753 healthy subjects. The genotyping of CETP (rs5882 and rs708272) was performed using a real-time PCR method. Results: After statistical analysis we found that CETP rs708272 genotype G/A under the over-dominant model was associated with the decreased odds of PA (OR=0.637; 95%CI: 0.443-0.917; P=0.015), active PA (OR=0.538; 95%CI: 0.335-0.865; P =0.01) and non-recurrent PA (OR=0.602; 95% CI: 0.402 - 0.902; P =0.014). When compared to controls, the rs708272 genotype G/A was less frequent in the active PA subgroup (37.5% vs 52.7%, P =0.009) and the non-recurrent PA subgroup (40.2% vs 52.7%, P=0.013), while the rs5882 genotype A/A was less frequent in the non-recurrent PA subgroup (37.5% vs 46.2%, P=0.015). Conclusion: Our study showed that CETP rs708272 genotype G/A may be associated with a decreased risk of PA.
Keywords: pituitary adenoma; CETP rs5882; rs708272; gene polymorphism; tumor